Experimental and numerical investigation of a thermocline thermal energy storage tank. (5th March 2017) - Hoffmann, J.-F.; Fasquelle, T.; Goetz, V.; Py, X.
Highlights: An experimental and numerical study is performed on a small thermocline tank. Two particle diameters and five mass flows were tested. An optimum mass flow/a maximum efficiency is found for the two particle sizes. The model is used to define the best mass flow for any particle diameter. Abstract: Thermocline thermal energy storage technology consists in separating hot fluid from cold fluid thanks to a clever use of buoyancy forces. The energy is therefore stored in one tank instead of two and the tank can be filled with solid materials to cut costs. However, the storage efficiency depends on several parameters such as the fluid mass flow and the size of the particles. In the present study, an experimental investigation has been performed in order to know how these parameters influence the size of the thermocline and the efficiency during charging and discharging. Various mass flows, from 0.01 kg s −1 to 0.05 kg s −1 were tested and two different size of particles were investigated (diameters of 12 mm and 40 mm, respectively). As a conclusion, the smaller the particle size, the better the storage efficiency, due to better heat transfer between fluid and solid. An optimum velocity can be found for each configuration of the tank: below this value, heat losses are too important, and above this value thermal flux carried by the forced convection of the heat transfer fluid is too important in comparison with the heat flux exchanged between fluid and solid. A previously validated numerical model has been used in order to verify its capacity of predicting the thermocline behavior, and in order to better understand the influence of the studied parameters on the storage performances. The model limits were found for high mass flows. It has been also shown that the mass flow needs to be chosen in accordance with the particle diameter in order to have maximum efficiency.